MODEL PEMBELAJARAN PAIKEM DI SEKOLAH DASAR: ANTARA TEORI DAN IMPLEMENTASI DI KELAS - Imam Mahdi Alfarezi (Jurnal Salome : Multidisipliner Keilmuan, 2026)
This study aims to examine the PAIKEM learning model (Active, Innovative, Creative, Effective, and Enjoyable Learning) in elementary schools by analyzing the gap between its theoretical foundations and classroom implementation. The method used is a literature review of various references including journals, books, and educational policy documents related to PAIKEM. The findings indicate that theoretically, PAIKEM is designed to create a student-centered learning environment that promotes active engagement, creativity, and meaningful learning. However, in practice, classroom implementation still faces numerous obstacles such as limited teacher competence, inadequate facilities, and a teacher-centered learning culture. This study concludes that strengthening teacher capacity through continuous training and concrete policy support is essential for optimal implementation of PAIKEM at the elementary school level.